Analisis Fenomena Ghosting pada Intimitas Relasi di Kalangan Mahasiswa Yogyakarta Melalui Pendekatan Fenomenologi Interpretatif - Hafidzotus Sa’adah Al Wahidah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The phenomenon of ghosting frequently occurs in interpersonal relationships, particularly among university students, and is often experienced in relationships that have developed relational intimacy. This study aims to understand and explore the phenomenon of ghosting within relational intimacy among students in Yogyakarta using an interpretative phenomenological approach. This research employs a qualitative method through in-depth interviews with five student informants aged 18–25 years in Yogyakarta who have experienced ghosting as perpetrators, victims, or both. Data were analyzed using Interpretative Phenomenological Analysis (IPA) through stages of repeated transcript reading, exploratory commenting, identification of emergent themes, and the development of superordinate themes. The findings indicate that ghosting is understood as a unilateral termination of a relationship without open communication within relational intimacy. Ghosting emerges as a relational process preceded by changes in interaction patterns in the form of relational distancing, which are associated with incompatibility, loss of comfort, and efforts to avoid conflict within the relationship.